Kedaulatan Fiskal dan Penguatan Otonomi Daerah Dalam Pemungutan Retribusi Pasca Undang-Undang Nomor 1 Tahun 2022 - I Gede Druvananda Abhiseka; I Putu Edi Rusmana; Febriansyah Ramadhan (JURNAL RECHTENS, 2025)
The purpose of this study is to examine the extent to which the sovereignty in the collection and sustainable development of regional retribution is implemented. This paper employs normative legal research. “The results of the study indicate that the form of sovereignty in the collection and development of regional retribution after the enactment of the Law on Financial Relations between the Central Government and Regional Governments” is limited, as the central government retains the authority to adjust tax and/or retribution rates stipulated in Regional Regulations on Taxes and/or Retributions through presidential regulations. Therefore, it can be concluded that regional governments do not yet fully possess fiscal sovereignty. It is recommended that the government promptly complete all implementing regulations for the amended provisions to ensure the smooth administration of regional retribution and the continued operation of regional autonomy, while maintaining the essence of regional sovereignty both in terms of autonomy and fiscal authority.